Analyses of orientation dependent nanoindentation response of pseudoelastic NiTi alloy using a crystal plasticity model. (August 2019) - Dhala, Satyabrata; Mishra, Sushil; Tewari, Asim; Alankar, Alankar
Highlights: Nanoindentation simulations of NiTi SMA conducted using crystal plasticity. The model includes phase transformation, dislocation glide and twinning. Load-depth responses, inelasticity and martensite volume fraction evolution of different crystallographic orientations are investigated. The effect of temperature on local surface morphology, crystallographic orientation, evolution of martensite volume fraction is analyzed. Abstract: In the present study, a crystal plasticity finite element model has been employed to mechanically characterize small scale deformation in pseudoelastic NiTi shape memory alloy (SMA) single crystal during nanoindentation. The model includes various inelastic mechanisms of deformation such as austenite to martensite transformation, dislocation glide in the austenite phase and twinning in the martensite phase. Simulations were conducted for nanoindentation of single crystals of NiTi along various crystallographic orientations and temperatures. The simulation results have been validated by comparing against experimental observations reported in the literature. The load-depth curves for various crystallographic orientations are consistent with the experimental results. The total martensite volume fraction is predicted and compared among the three orientations. Furthermore, in order to study the effect of temperature on deformation characteristics during nanoindentation of NiTi SMA, simulations are carried at two different temperatures. The results show the depth recovery ratio and the slope of the load-depth curve increase with the increase of temperature. The simulation results are satisfactorily consistent with the experimental results. The martensite volume fraction evolution and surface profile of the indentation surface are also analyzed.